Peran Pemerintah Daerah Dalam Penanggulangan Kemiskinan di Kabupaten Jeneponto - Ahmad Zihar Mubaraq (Departemen Ilmu Pemerintahan Fisip Unhas, 2024)
This study aims to examine and analyze the role of local government in poverty alleviation in Jeneponto Regency and the factors that influence it. The type of research used is qualitative research. The location of this research is Jeneponto Regency. Meanwhile, the types of data used are primary and secondary data. Data collection techniques used are observation, interviews, literature studies, and documentation. The data analysis technique used is qualitative analysis. The results of the study indicate that the role of local government in poverty alleviation in Jeneponto Regency, when viewed and measured through the government's role as a regulator, dynamicator, and facilitator, has been running quite well, but still needs to be improved, especially in strengthening the budget, increasing public awareness, and updating poverty data.